Through the teacher’s lens: Evaluation of the project-based curricula of Philippine and Japanese science high schools - Leo Peter Dacumos; Masakazu Kita (SEAQIS Journal of Science Education, 2021)
Specialized science, technology, engineering, and mathematics (STEM) high schools provide intensive learning experiences for advanced learners. At the core of these STEM schools is a project-based (research) curriculum that aims to foster research culture among learners, creating critical thinkers and problem-solvers, preparing them to be globally competitive STEM professionals in the future. The Philippine STEM junior high schools system and Japan’s Super Science High (SSH) are amongst implementers of the project-based (research) curricula. Hence, this paper sought to conduct a critical review of these project-based curricula through quantitative analysis of Filipino and Japanese teachers’ perceptions of its effectiveness along the four dimensions of Tyler’s Objective-centered Model for curricular evaluation. Findings show similarities and significant differences in the perception of the project-based curricula' effectiveness between Filipino and Japanese teachers along the four dimensions of Tyler’s Objective-centered Model: (1) learning objectives; (2) learning experiences; (3) organization of learning experiences; and (4) evaluation methods.